Obtaining natural dye from anthocyanins extracted from molasses grass (Melinis minutiflora P. Beauv.) and study of its application in yogurts (Research, Society and Development, 2022)
The consumption of artificial dyes has been worrying consumers, driving research on natural dyes and their application in food. Anthocyanins are a class of compounds with potential for use as food coloring, due to their abundance in nature, wide range of colors and beneficial health effects, with proven antioxidant capacity. Molasses grass (Melinis minutiflora) is a promising source of anthocyanins due to its low cost and the presence of methylated anthocyanins in its composition. The objective of the present work was to obtain a natural dye from molasses grass anthocyanins and its application in yogurts. The extraction of anthocyanins from molasses grass was optimized by a Central Composite Rotational Design (DCCR) with two variables, eight trials and three central points, where the optimal conditions of 15 g of grass to 50mL of extracting solution, with 38.5% ethanol. The extracts obtained from the optimal conditions were rotaevaporated to remove the ethanol and lyophilized, getting a concentrated dye. Two types of yogurts were produced, with and without applying the dye and evaluated for pH, acidity, water holding capacity and color during 27 days of storage. The yogurts showed good storage stability, reducing the color intensity to levels not perceptible to the unaided human eye. The results showed the potential of using natural dye from molasses grass for this type of food matrix.